Organizations in Time - Bucheli, Marcelo; Wadhwani, R. (Ascent Audio, 2019)
Why does history matter to our understanding of management, organizations, and markets? What theoretical insights can it offer into organizational processes? How can scholars use historical sources and methods to address research questions in management and organization studies? This book brings together leading organization scholars and business historians to examine the opportunities and challenges of incorporating historical research into the study of firms and markets. It examines the reasons for the growing interest in historically grounded research in management departments and business schools, and considers both the intellectual and practical questions the endeavor faces.